Healing Power of Sound - van Otterloo, Nils de Mol; Sudan, Nimit; Lyons, Matthew; Nair, Murali (International Journal of Innovative Research in Medical Science, 2016)
This article discusses the healing powers of sound and its diverse applications, ranging from ancient teachings and practices to present-day evidence-based studies. Various cultural, geographical, scientific, spiritual, and religious perspectives have been gathered to illustrate the many ways sound is utilized to improve human well-being.